Internet Communications and Political Mobilization - Avzalova, Elmira (International Journal of Criminology and Sociology, 2022)
The paper is devoted to the consideration of the role of Internet communications in the political mobilization of citizens. Internet communications create new opportunities for interaction and association of citizens and significantly accelerate political mobilization. In the information age, the "orange revolutions", and other "colour revolutions" of the last century were replaced by high-tech "network revolutions". Among researchers, however, there is no unity in understanding the role of Internet communications in mobilizing the protest activity of the population. The article concludes that when assessing the role of Internet communications in political mobilization, it is important to take into account the fact that the Internet communications are not capable of causing revolutionary events, popular actions were generated by a number of socio-economic, political and ideological reasons. However, social networks and microblogging services have become new tools for mobilizing participants in protests, allowing campaigning and coordination among protesters.